Evaluation of Wound Healing Properties of Dryopteris filix-mas Leaf and Root Extracts on Albino Rats: Wound Healing Potentials of Dryopteris filix-mas on Albino Rats - Oghenesuvwe Erhirhie, Earnest; Odinakachi Anyim, Cathrine; Moses Okezie, Ugochukwu; Obiora Igboeme, Sabastine; Emeka Ilodigwe, Emmanuel (Iranian Journal of Pharmaceutical Sciences, 2021)
Dryopteris filix-mas (D. filix-mas), belonging to the family of Dryopteridacea is a swampy fern that is popularly used by the Southern Nigerian dwellers in the treatment of wounds, hemorrhages, boil and other diseases. In order to authenticate its folkloric benefits in wounds, this study evaluated its wound healing activity using excision model. A total of fifty (50) Wistar rats were randomized into ten groups of five animals each. After creation of surface wounds, group 1 received paraffin base (control). Group 2 received Povidon iodine (standard). Groups 3, 4, 5 and 6 received 1.25, 2.5, 5 and 10% (w/w) of an ethanol leaf extract of D. filix-mas formulated with paraffin base respectively. Groups 7, 8, 9, 10 were treated with 1.25, 2.5, 5 and 10% (w/w) of ethanol root extract D. filix-mas formulated with paraffin base respectively. Treatments were topically applied to wounds once daily and healing rate was monitored every 3 days for 21 days. Wound swaps were taken on day 10th and day 20th for bacteria load determination. In-vitro antimicrobial activities of the leaf and root extract were tested against Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli using agar-well diffusion method. Higher concentrations (5 and 10%) of the leaf and root extracts exhibited better wound healing activities more than lower concentrations. The leaf extract produced a better healing rate (wound contraction), antimicrobial activity and body weight regaining activities more than the root extract. This study validates the traditional use of D filix-mas in the treatment of wounds.